An Exploration of Teachers' Beliefs about the Role of Grammar in Iranian High Schools and Private Language Institutes - sasan baleghizadeh; Sepideh Farshchi (Journal of English Language Teaching and Learning, 2009)
This study was an attempt to explore the beliefs of Iranian EFL teachers about the role of grammar in English language teaching in both state schools and private language institutes. Data were collected through a questionnaire developed by Burgess and Etherington (2002), which consisted of 11 main subscales and was divided into two sections. The first section dealt with approaches to grammar teaching and the second with student and teacher difficulties with grammar. An independent sample t-test was used on all the eleven subscales to check the differences among teachers’ beliefs in both state and private language schools. Responses from 117 English language teachers from both settings indicated that they appreciate the value of grammar and its role in language teaching. However, their beliefs were significantly different in three areas: explicit teaching of grammar, the role of instruction versus exposure, and presentation of grammar through authentic texts.